Extrusion of instrument to periapical tissues and resolution by periapical surgery: a case report - Villalpando-Lazcano, Jesús Israel (2019)
The fracture of manual or rotatory instruments is one of the most common complications that occurs during the root canal treatment. Removing the instrument from inside of the canal is the ideal procedure, however, there are cases in which is impossible to remove it, so, a periapical surgery is needed. In this case, we explain how an endodontic instrument fractured in the apical third of a first low premolar was extruded to periapical tissues when using ultrasound to attempt to remove it, for this reason an apicectomy was performed on the compromised dental organ.